High occurrence of viruses in the mucus layer of scleractinian corals. Issue 6 (9th July 2014) - Nguyen‐Kim, Hanh; Bouvier, Thierry; Bouvier, Corinne; Doan‐Nhu, Hai; Nguyen‐Ngoc, Lam; Rochelle‐Newall, Emma; Baudoux, Anne‐Claire; Desnues, Christelle; Reynaud, Stéphanie; Ferrier‐Pages, Christine; Bettarel, Yvan
Summary Viruses attract increasing interest from environmental microbiologists seeking to understand their function and role in coral health. However, little is known about their main ecological traits within the coral holobiont. In this study, a quantitative and qualitative characterization of viral and bacterial communities was conducted on the mucus of seven different coral species of the Van Phong Bay (Vietnam). On average, the concentrations of viruses and bacteria were, respectively, 17‐ and twofold higher in the mucus than in the surrounding water. The examination of bacterial community composition also showed remarkable differences between mucus and water samples. The percentage of active respiring cells was nearly threefold higher in mucus (m = 24.8%) than in water (m = 8.6%). Interestingly, a positive and highly significant correlation was observed between the proportion of active cells and viral abundance in the mucus, suggesting that the metabolism of the bacterial associates is probably a strong determinant of the distribution of viruses within the coral holobiont. Overall, coral mucus, given its unique physicochemical characteristics and sticking properties, can be regarded as a highly selective biotope for abundant, diversified and specialized symbiotic microbial and viral organisms.